Implementation of bibliometric techniques for minority tongues musical heritage study - Fernández-Abad, Francisco Javier (Revista General de Información y Documentación, 2023)
This piece of work studies musical heritage created by the different national minority tongues for the purpose of obtaining technic documentation to be used for desing of promotional politics and linguistic planification. For this object, we suggest import bibliometric methodologies to the sociolinguistic área showing its viability and adaptation. We focuss on production of musical asturian, aragonese and aranese-occitan languages collecting the whole musical documents from 1981 to 2020 recopilated on public record office of National Radio of Spain situated in Prado del Rey. As a result, it posible to find out the different of productivity marks doing small methodologic fixes.